Rootstock trial of eight GxN interespecific hybrids in almond - Bielsa B.; Rubio-Cabetas J.M.; Felipe A.J.; Gómez-Aparisi J.; Socias i Company R. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Almond growing is increasingly extending to areas where the species is not truly suited to, despite favourable climate. The most common problems in many Mediterranean countries include replanting, limestone chlorosis, and soilborne pests and diseases such as Meloidogyne root-knot nematodes and Armillaria mellea root-knot. Several almond x peach hybrids have shown good performance as rootstocks for different stone fruit species, including almond. The first commercially known hybrid was ‘GF- and it is still used worldwide and demanded at present for almond growing. Eight almond x peach hybrids from the CITA breeding programme were evaluated in a rootstock trial located at CITA. They were grafted with the almond selection ‘B-2- in 1994 and planted in 1995 at a distance of 5 ×, using ‘GF- and ‘Nemared’ as controls. The trunk cross sectional area (TCSA) and productivity were evaluated. The results showed a differential performance for production and vigour between the ‘GF- and ‘Nemared’ as compared to the GxN series. Some differences were also observed for vigour among the three already commercially propagated ‘Garnem’ ‘Felinem’ and ‘Monegro’.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)